The Impact of Implementing Positive Culture-Based Classroom Management on Reducing Students' Disruptive Behaviors - Aski; Astuti A (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2025)
This thesis discusses the Impact of Implementing Positive Culture-Based Classroom Management on Reducing Disruptive Behavior at SDN 84 Watang Cenrana, Bone Regency. The purpose of this study is to determine the Impact of Implementing a Positive Culture-Based Classroom Management Model on Reducing Disruptive Behavior. The type of research used in this study is qualitative data. This study uses a management, pedagogical and child psychology approach. In collecting data using observation, interview and documentation methods. In this study the objects of the interview were class teachers, homeroom teachers and students. The results of the study show that 1) The role of positive culture-based classroom management at SDN 84 Watang Cenrana, Bone Regency plays a very important role. Overall, it can be concluded that the role of positive culture-based classroom management is very vital in transforming class dynamics. Its implementation has proven effective in minimizing negative behavior and significantly increasing student involvement and active participation. 2) The application of positive culture-based classroom management on reducing the level of disruptive behavior of students at SDN 84 Watang Cenrana, Bone Regency. The application of positive culture-based classroom management has a crucial role in suppressing disruptive behavior of students. Through the habituation of virtue values, the formation of mutually agreed class beliefs, and the application of problem-solving strategies using the restitution triangle, students are encouraged to understand the consequences of their actions and take responsibility for their behavioral choices.